Mental health services and their relation with nursing education - Soares, Amanda Nathale (2010)
Teaching on psychiatric nursing and mental health in undergraduate nursing programs at Federal Universities around the Brazil uses conceptions and care technologies that should be in line with the mental health services used as practical teaching areas for this subject. It is an exploratory case study, using a questionnaire sent to the faculty members responsible for psychiatric nursing and mental health subjects The objective of this research is to analyze the extra-hospital mental health services used as practical areas for nursing students from the perspective of nursing education. The mental health services used as practice areas in this study were all substitutive, mostly CAPS II, with similar objectives and activities as well as physical conditions that differ according to the region they are placed. The conclusion is that training areas used incite education in line with the principles of the Psychiatric Reform.